A Life of Sir Harry Parkes : British Minister to Japan, China and Korea, 1865-1885 - Morton, Robert, 1965- (Book collections on Project MUSE., 2021)
Harry Parkes was at the heart of Britain's relations with the Far East from fourteen, to his death at fifty-seven. In his day, he was seen as both a hero and a monster and is still bitterly resented in China for his part in the country's humiliations at Western hands, but largely esteemed in Japan for helping it to industrialise.